Clinical electrophysiological effects of atenolol--a new cardioselective beta-blocking agent. Issue 1 (January 1978) - Robinson, C; Birkhead, J; Crook, B; Jennings, K; Jewitt, D
Abstract : Atenolol, a cardioselective beta-blocking agent, at dose levels of 0.03, 0.06, and 0.12 mg/kg intravenously, produced prolongation of atrioventricular nodal conduction in 22 patients with suspected coronary artery disease. In a dose of 0.12 mg/kg body weight atenolol produced significant prolongation of sinus cycle length, sinus node recovery time, atrioventricular node conduction, and the effective and functional refractory periods of the atrium and the atrioventricular node. No significant effects were observed on the His Purkinje system or the effective refractory periods of the ventricle. In these actions atenolol closely resembles propranolol. However, because in contrast to propranolol it increases atrial refractoriness, it may have advantages in the treatment of atrial arrhythmias.